2002
DOI: 10.5194/hess-6-539-2002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen concentrations in a small Mediterranean stream: 1. Nitrate 2. Ammonium

Abstract: The importance of storm frequency as well as the groundwater and hyporheic inputs on nitrate (NO 3 -N) and ammonium (NH 4 -N) levels in stream water were studied in a small perennial Mediterranean catchment, Riera Major, in northeast Spain. NO 3 -N concentrations ranged from 0.15 to 1.9 mg l -1 . Discharge explained 47% of the annual NO 3 -N concentration variance, but this percentage increased to 97% when single floods were analysed. The rate of change in nitrate concentration with respect to flow, ∆NO 3 -N/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
(35 reference statements)
3
17
0
Order By: Relevance
“…The counterclockwise hysteresis in NO À 3 concentrations during heavy rainfall (Fig. 6-b) suggests the contribution of groundwater to the NO À 3 concentration in streams (Butturini and Sabater 2002). Thus, heavy rainfall events cannot be ignored in studies of NO À 3 fluxes.…”
Section: Possible N Saturationmentioning
confidence: 97%
“…The counterclockwise hysteresis in NO À 3 concentrations during heavy rainfall (Fig. 6-b) suggests the contribution of groundwater to the NO À 3 concentration in streams (Butturini and Sabater 2002). Thus, heavy rainfall events cannot be ignored in studies of NO À 3 fluxes.…”
Section: Possible N Saturationmentioning
confidence: 97%
“…Nutrient and solute concentrations in stream ecosystems generally are related to the characteristics of the surrounding watershed [ Aiken and Cotsaris , 1995; Allan and Johnson , 1997; Aryal et al , 2003; Boyer et al , 2000; Findlay et al , 2001; Heiny and Tate , 1997] and changes in land cover and land use often are reflected in stream and river chemistry. Semiarid regions throughout the world are experiencing substantial population growth and consequently urban expansion, which ultimately alters the characteristics of the watershed [ Butturini and Sabater , 2000, 2002; Parks and Baker , 1997; Steiner et al , 2000; Stromberg et al , 1996; Westerhoff and Anning , 2000], but how and if this land use change affects stream biogeochemical cycling remains an open question. The conversion of the natural landscape to agricultural or residential land uses can cause an increase in sedimentation and nutrient, particularly nitrogen, concentrations, especially when combined with the encroachment of nitrogen‐fixing species such as mesquite [ Allan and Johnson , 1997; Findlay et al , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…First, storm flow induces hysteresis in the instantaneous interaction of stream discharge and DIN and SO 4 2 exports, which leads to large errors in estimates of annual DIN and SO 4 2 exports (Takeda, 2001). The hysteresis pattern is caused by the different concentrations between rising and receding limbs of a hydrograph for DIN (Ávila et al, 1992;Evans et al, 1999;Butturini and Sabater, 2002;Zhang et al, 2007) and SO 4 2 (Ávila et al, 1992;Rose, 2003). Second, storm flow sampling is time consuming, which increases the costs related to water sampling and chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that concentrations are different between storm 632 M. CHIWA ET AL. and low flow periods for NO 3 (Edwards, 1973;Muraoka and Hirata, 1988;Ávila et al, 1992;Murdoch and Stoddard, 1993;Creed and Band, 1998;Ohrui and Mitchell, 1998;McHale et al, 2000;Butturini and Sabater, 2002;Yusop et al, 2006) and SO 4 2 (Edwards, 1973;Ávila et al, 1992). Therefore, estimates of DIN and SO 4 2 exports that were extrapolated from concentrations during low flow periods and storms would be biased, unless the relationship between discharge and DIN or SO 4 2 concentration in stream water was similar between the low and storm flow periods.…”
Section: Introductionmentioning
confidence: 99%